Synthesis of a novel terpolymer of (BA-co-SMA-co-MA) as pour point depressants to improve the flowability of the Malaysian crude oil - Elganidi, Ibrahim; Elarbe, Basem; Norida, Ridzuan; Norhayati, Abdullah (Elsevier Ltd, 2020)
During the extraction of crude oil, the reservoir temperature is much higher than the surface temperature especially when the oil is transported cross subsea. Therefore, the flow of virgin oil gets impeded due to the precipitation of wax on the inner wall of pipelines when the temperature decreased below the wax appearance temperature (WAT) and the flow stops if the temperature falls below the pour point.Polymeric pour point depressants (PPD) have received considerable attention as a wax control approach to enhance the flowability of waxy crude oil. The aim of the current study is to synthesize a novel PPD of benhely acrylate-co-stearyl methacrylate-co-maleic anhydride (BA-co-SMA-co-MA) to improve the viscosity of Malaysian crude oil using free radical polymerization. The effect of polymerization parameters, such as reaction temperature, initiator concentration, experimental duration, and monomer concentration on the yield of the synthesized polymer was evaluated statistically with a one-factor-at-a-time (OFAT) approach. The performance of the prepared PPD was evaluated to determine its effects on the viscosity of crude oil using Brookfield DV-III viscometer. The experimental results showed that the optimum conditions to obtain the highest yield were at the reaction time of 8 h, initiator concentration of 1.5 wt%, reaction temperature of 100 C, and monomers ratio of (BA:SMA: MA) 1:1:1. At the optimum conditions, the prepared terpolymer reduces the viscosity of crude oil from 7.2 mPa.s to 3.2 mPa.s at 30 C using 1500 ppm. The significant reduction in the apparent viscosity indicated improvement in the lowtemperature flow properties of the crude oil after applying the synthesized PPD